Elders Health Empowerment Scale. Spanish adaptation and psychometric analysis (Colombia Medica, 2014)
Introduction: Empowerment refers to patient skills that allow them to become primary decision-makers in control of daily self-management of health problems. As important the concept as it is, particularly for elders with chronic diseases, few available instruments have been validated for use with Spanish speaking people. Objective: Translate and adapt the Health Empowerment Scale (HES) for a Spanish-speaking older adults sample and perform its psychometric validation. Methods: The HES was adapted based on the Diabetes Empowerment Scale-Short Form. Where “diabetes” was mentioned in the original tool, it was replaced with “health” terms to cover all kinds of conditions that could affect health empowerment. Statistical and Psychometric Analyses were conducted on 648 urban-dwelling seniors. Results: The HES had an acceptable internal consistency with a Cronbach’s α of 0.89. The convergent validity was supported by significant Pearson’s Coefficient correlations between the HES total and item scores and the General Self Efficacy Scale (r= 0.77), Swedish Rheumatic Disease Empowerment Scale (r= 0.69) and Making Decisions Empowerment Scale (r= 0.70). Construct validity was evaluated using item analysis, half-split test and corrected item to total correlation coefficients; with good internal consistency (α> 0.8). The content validity was supported by Scale and Item Content Validity Index of 0.98 and 1.0, respectively. Conclusions: HES had acceptable face validity and reliability coefficients; which added to its ease administration and users’ unbiased comprehension, could set it as a suitable tool in evaluating elder’s outpatient empowerment-based medical education programs.